(untitled) (La U Investiga, 2018)
Objective: To compare the sociocultural factors associated with adolescent pregnancy in the Canton Carlos Julio Arosemena Tola, from January to June 2018, for which non-pregnant adolescents between the ages of 10 and 19 years were compared with pregnant adolescents of the same age. Methods: cross-sectional, prospective, observational, analytical study, in a period of 6 months, in the Canton Carlos Julio Arosemena Tola, Province of Napo, in the period from January to June 2018. We worked with the total of adolescent women which are 417, of which 10 are in gestation period. We excluded 70 adolescents from the study, of whom 68 did not meet the inclusion criteria (not nulliparous) and 2 adolescents of 19 years who could not be located when they were studying outside the Canton. The measures of central tendency and dispersion were established with the numerical variables, with the qualitative variables proportions were defined. Statistical analysis x2 was used as a nonparametric test to establish statistical significance. Results: it was proved that sociocultural factors such as: beginning of sexual life especially in middle adolescence, secondary education, not being a student, single marital status, nuclear family and family dysfunction are related to teenage pregnancy with a value of p<0.05 and a 95% CI. These sociocultural risk factors predict in 89.3% the development of teenage pregnancy in Arosemena Tola, 2018. Conclusions: sociocultural factors such as: beginning of sexual life especially in middle adolescence, secondary education, not being a student, single marital status, nuclear family and family dysfunction are related to teenage pregnancy, the same ones that predict in a high percentage of adolescent pregnancy development in the Canton Carlos Julio Arosemena Tola, in the study period.